Essential cell-intrinsic requirement for GMDS in T cell development - Yabas, Mehmet; Roots, Carla M.; Andrews, T. Daniel; Field, Matt A.; Goodnow, Christopher C.; Enders, Anselm (Frontiers in Immunology, 2025)
Fucosylation, a type of glycosylation, is the attachment of a fucose to N-glycans, O-glycans and glycolipids, and is critical for the post-translational regulation of many essential pathways. Here we describe a mouse strain with an N-ethyl-N-nitrosourea-induced point mutation in the gene encoding guanosine diphosphate (GDP)-mannose 4,6-dehydratase (GMDS), an enzyme involved in the generation of GDP-fucose, a substrate for fucosylation. GmdsY187*/Y187* mice displayed growth retardation and increased postnatal mortality. Immunophenotyping of GmdsY187*/Y187* mice revealed reduced numbers of double positive (DP), CD4 single positive (SP) and CD8SP T cells, despite normal numbers of double negative (DN) cells in the thymus of mutant animals. Similarly, analysis of the thymus in Rag1-/- mice reconstituted with GmdsY187*/Y187* bone marrow cells revealed a partial arrest at the DN stage of T cell development compared to animals transplanted with Gmds+/+ bone marrow cells. Furthermore, mixed chimeras showed that GmdsY187*/Y187* T cells were unable to compete with Gmds+/+ cells from the DP stage of T cell development in the thymus. This inability to compete resulted in the near absence of GmdsY187*/Y187*-derived peripheral T cells in recipient mice, while B cell subsets were present at broadly normal frequencies. These findings provide the first evidence of an essential cell-intrinsic requirement for GMDS in early T cell development in mice.